An audit of infection control practices in Central Sterile Supply Department in a Tertiary Care Hospital, Puducherry - Savitha B Hiremath; B V Renushree; R Vinod; P Shilpa (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Central Sterile Supply Department (CSSD) has broadened its significance from just an area where things just come cleaned and go with an autoclave machine to a huge department which regulates all the practices with standard procedures and has a huge role in infection control practices. A good CSSD indicates a good hospital infection control setup. We are nowadays more focused on standard practices following appropriate guidelines that can prevent nosocomial infections. CSSD has a huge role to play in the assurance of sterility check and the traceability of all the sterilized instruments for any suspected outbreaks from CSSD. OBJECTIVES: The objectives of this study were (1) to audit the existing infection control practices in CSSD in a tertiary care hospital, (2) to implement the Infection control practices in the study area, and (3) to evaluate the impact of the progress after implementing changes in the study area. METHODOLOGY: This is a descriptive interventional and hospital-based study carried out in Sri Venkateshwaraa Medical College Hospital and Research Centre, Puducherry. The tools for the audit include questionnaire. Data was analyzed by SPSS 23.0 (IBM Corp. Released 2015.SPSS Statistics 23 for Windows, Armonk, New York, United States). RESULTS: Pretest results for various questions ranged from 20% to 100% among the participants. The posttest was conducted after the training and teaching of and showed 100% results among all the participants. CONCLUSION: We conclude that the auditing done in CSSD had basic knowledge of the needs and facilities. Implementation of practices in CSSD had been a huge learning process for all of us and was very fruitful. The impact of progress has been shown with the improvised quality of work being done now at various stages of CSSD.